مؤشرات الفضاء الانتقالي لدى الطفل المنفصل عن أمه - علاف, شهيرة (جامعة الوادي - University of Eloued, 2022)
ملخص: تعتبر الطفولة مرحلة حاسمة في تحديد شخصية الفرد و تكوينها، فهي تحتاج إلى مساعدة مكثفة من طرف الوالدين و خاصة الأم من خلال عنايتها الوجدانية و معاملتها و توظيفها لجسم الطفل بلمسه و ملاطفته و الاعتناء به؛ يمنح للفضاء الانتقالي أهمية بالغة في السنوات الأولى من نمو الطفل، إذ تعد تجربة الشعور بالتموضع فيه باستعمال الموضوع الانتقالي المادي تأسيسا لشعوره بذاته، حيث تمنحه الأم القدرة على امتلاك هذا الموضوع بموافقتها فهو يحمل تجارب رائعة مشتركة معها تساعده على تحمل قلق الانفصال؛ تخلي الأم عن طفلها في هذه المرحلة يؤدي إلى متابعة حياته بعيدا عن جو الأسرة و الوالدين كطفل منفصل عن عائلته البيولوجية. لذا قمنا بإجراء هذا البحث بهدف تعميق معرفتنا بالسير النفسي للطفل المنفصل عن أمه في سن مبكرة و تحديدا البحث عن المؤشرات الدالة عن إمكانية أو صعوبة تموضعه في فضاء انتقالي من خلال تطبيق تقنية المقابلة العيادية و اختبار الرورشاخ الإسقاطي. Abstract: Childhood is a crucial stage in defining the personality. It needs intensive help from the parents, especially the mother, through her emotional care, treatment and caring; the transitional space is given great importance in the early years of a child’s development, as the experience of feeling positioned in it by using the material transitional subject. Where the mother gives him the ability to own this subject, he has wonderful experiences in common with her that help him bear separation anxiety; The mother's abandonment of her child at this stage leads to him continuing his life away from the atmosphere of the family and parents. Therefore, we conducted this research with the aim of deepening our knowledge of the psychological functioning of the child separated from his mother at an early age, and specifically the search for indicators of the possibility or difficulty of being positioned in a transitional space through the application of the clinical interview technique and the projective Rorschach test.
دراسة حالة من خلال المقابلة العيادية و اختبار الرورشاخ الإسقاطي
مقال
Keywords: فضاء انتقالي ; انفصال عن الأم ; اختبار الر ; رشاخ الإسقاطي; Transitional Space, Separation from mother, the projective test of Rorschach